The Change of the Average Monthly Precipitation Rates in Beregszász Between 1947 and 2009 - Izsák Tibor; Іжак Тібор; Izhak Tibor (PoliPrint Kft., 2012)
Abstract. The article determines the change of the amount of precipitation in Beregszász in the period from 1947 to 2009 on the basis of the Beregszász meteorological station’s monthly data. The data were statistically processed with the help of the linear trend analysis and Microsoft Excel software. In the process of the research the author has determined that the amount of precipitation in Beregszász in the last 63 years has grown and testifies to significant changes. Precipitation is not distributed evenly during the months, there is no system seen in the changes. The data obtained prove that in the period under analysis the average monthly amounts of precipitation according to trend lines were gradually increasing, however showed significant change only in September.

Резюме. Метою статті було визначити зміну величини кількості опадів у місті Берегові. За основу були взяті дані Берегівської метеорологічної станції про кількість місячних опадів з 1947 по 2009 роки. Обробка даних проводилася за допомогою лінійного аналізу тенденцій з використанням програми Microsoft Excel. Дослідження засвідчили, що величина кількості опадів у місті Берегові за останні 63 роки підвищилася. Опади протягом року та по місяцах розподілялися нерівномірно, регулярність не спостерігалася. На основі лінійного аналізу тенденцій дані вказують, що за досліджуваний час кількість середньомісячних опадів поступово підвищувалася, але значні зміни відбулися тільки за вересень місяць.
https://www.kmf.uz.ua/hun114/letoltes/acta/Acta_2012_2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00005840
Keywords: precipitation rate; weather; rainfall; Beregszász